Novel genotypes and phenotypes in Snijders Blok-Campeau syndrome caused by CHD3 mutations - Gao, Yuanyuan; Wang, Pei; Chen, Mengying; Pang, Kexin; Sun, Yifan; Zheng, Bixia; Li, Taisong; Zhang, Hongmei; Zhu, Min (Frontiers in Genetics, 2024)
Background: Snijders Blok-Campeau syndrome (SNIBCPS) is a rare genetic disorder characterized by facial abnormalities, hypotonia, macrocephaly, and global developmental delay (GDD) caused by mutations in CHD3 gene. There is limited information on SNIBCPS and few studies on its pathogenic gene CHD3. Methods: We utilized whole-exome sequencing, in vitro minigene splicing assay analysis, and construction of protein models to validate the suspected pathogenic mutation. In addition, the PubMed database was searched using the keywords "Snijders Blok-Campeau syndrome", "CHD3", or "SNIBCPS" to summarize the gene mutations and clinical phenotypic characteristics of children with SNIBCPS. Results: We identified a non-frameshift variant c.3592_c.3606delGCCAAGAGAAAGATG, a splice site variant c.1708-1G>T, and two missense variants, c. 2954G>C (p.Arg985Pro) and c.3371C>T(p.A1124V), in CHD3 variants with SNIBCPS. Importantly, the c.3592_c.3606delGCCAAGAGAAAGATG, c.1708-1G>T, and c.3371C > T (p.A1124V) loci were not reported, and the children in this study also had phenotypic features of unibrow, transverse palmar creases, tracheal bronchus, and hypomelanosis of Ito (HI). The c.1708-1G>T classical splicing mutation leads to abnormal shearing of mRNA, forming a truncated protein that ultimately affects gene function. Conclusion: Our findings have expanded the spectrum of genetic variants and clinical features in children with SNIBCPS. Splicing analysis of CHD3 is an important method to understand the pathogenesis of spliced cells.